TSAQOFAH ISLAMIYAH SEBAGAI PILAR PENGUATAN IDENTITAS MAHASISWA PENDIDIKAN MAHASISWA ISLAM DI ERA GLOBALISASI - Khumaira, Ummi; Nurul Aini, Elsayanti; Nursyifa, Fayza Oktanika; Jannah, Shafira Miftakhul (Faculty of Islamic Studies, University of Muhammadiyah Jakarta, 2026)
The globalization era has transformed the landscape of Islamic education, particularly in shaping students‘ religious identity within increasingly secular, digital, and transnational contexts. Previous studies on Tsaqāfah Islāmiyyah have largely approached the concept from normative and moral perspectives, with limited analytical discussion on its function as a conceptual and epistemological framework for identity formation in Islamic higher education. This study aims to address this gap by examining the role of Tsaqāfah Islāmiyyah as a foundational framework for strengthening the identity of Islamic education students in the context of globalization. This study employs a qualitative library research method through a systematic review of classical and contemporary literature on Tsaqāfah Islāmiyyah, globalization, and Islamic education. The findings demonstrate that Tsaqāfah Islāmiyyah functions not merely as a moral guideline, but as an integrative intellectual framework that mediates between Islamic tradition and modern global knowledge. This framework contributes to the formation of students‘ epistemological orientation, critical awareness, and religious identity in responding to global challenges.